Characterisation of protein families in spider digestive fluids and their role in extra-oral digestion - André Walter; Jesper Bechsgaard; Carsten Scavenius; Thomas S. Dyrlund; Kristian W. Sanggaard; Jan J. Enghild; Trine Bilde (BMC Genomics, 2017)
Abstract Background Spiders are predaceous arthropods that are capable of subduing and consuming relatively large prey items compared to their own body size. For this purpose, spiders have evolved potent venoms to immobilise prey and digestive fluids that break down nutrients inside the prey’s body by means of extra-oral digestion (EOD). Both secretions contain an array of active proteins, and an overlap of some components has been anecdotally reported, but not quantified. We systematically investigated the extent of such protein overlap. As venom injection and EOD succeed each other, we further infer functional explanations, and, by comparing two spider species belonging to different clades, assess its adaptive significance for spider EOD in general. Results We describe the protein composition of the digestive fluids of the mygalomorph Acanthoscurria geniculata and the araneomorph Stegodyphus mimosarum, in comparison with previously published data on a third spider species. We found a number of similar hydrolases being highly abundant in all three species. Among them, members of the family of astacin-like metalloproteases were particularly abundant. While the importance of these proteases in spider venom and digestive fluid was previously noted, we now highlight their widespread use across different spider taxa. Finally, we found species specific differences in the protein overlap between venom and digestive fluid, with the difference being significantly greater in S. mimosarum compared to A. geniculata. Conclusions The injection of venom precedes the injection with digestive fluid, and the overlap of proteins between venom and digestive fluid suggests an early involvement in EOD. Species specific differences in the overlap may reflect differences in ecology between our two study species. The protein composition of the digestive fluid of all the three species we compared is highly similar, suggesting that the cocktail of enzymes is highly conserved and adapted to spider EOD.